Critical care obstetrics - Pacheco, Luis D.; Phelan, Jeffrey P.; Halscott, Torre L.; Moroz, Leslie A.; Vaught, Arthur J.; Saad, Antonio F.; Shamshirsaz, Amir A. (Wiley, 2024)
"For the current edition, we have added five new editors with extensive training and knowledge in critical care medicine. Each chapter has been revised and updated, and new chapters covering exciting topics such as ECMO, pneumonia, antibiotics, antivirals, and antifungals have been added. We hope the book serves to improve care of seriously ill pregnant patients around the world and stimulate younger generations to pursue excellence in maternal medicine"-- Provided by publisher.
Keywords: Pregnancy -- Complications.; elektronické knihy; electronic books